GELIAT POLITIK IDENTITAS DI KOTA MANADO - Muhammad Irfan Syuhudi (Harmoni, 2016)
This paper aims to describe the background of the establishment of identity politics in the city of Manado and how the identity politics develops in the city until today. The selection of informants was undertaken purposively. They are the board members who are still active and have ever been involved in the group identity, religious leaders, and academics, know the context of the research in the city of Manado. Data collection was done through interviews, observation, documentation, the use of internet to search for websites informing the context of the study. The research findings show taht identity politics came to the fore in the beginning of the reform era, which gave birth to the making of the group’s identity, among others are; Brigade Manguni Indonesia, Legium Christum, Laskar Manguni, Makapetor (Society Kawanua lover of tolerance ), and Militia Waraney. All these identity groups represent the indigenous ethnic group of Minahasa as the majority in the city. The development of these identity groups in Manado continues to evolve significantly. Besides, these groups turned out to have a hidden agenda to meet the interests of the group in politics and economics. Identity politics in Manado is fluid, not rigid, and does not trigger inter-religious conflicts to occur, although the Christian Minahasa is the dominat group identity.